CORAK PEMIKIRAN TEOLOGI ISLAM (STUDI KASUS PADA TOKOH AGAMA DI BENGKULU UTARA) - Syahril Syahril (Manthiq, 2016)
Abstract: This research by using qualitative  research methodologies. The results  of this study concluded that the idea  of religious figures of Islamic theology  in North Bengkulu  looked  sense can  serve to obtain  clarity on the  issues  of divinity in the  importance of reason necessary for aspects of Islamic  teachings are  informed by revelation.  Revelation  is a source of knowledge about  God, good and evil, as well as the obligation  of mankind to do good and keep away evil sense function, without revelation will bringheavy burden in human life. Meaning here, religious leaders in North Bengkulu wearing  traditional  pattern, although the one hand there is the rational or principled Mu’tazila. Thought religious leaders about  human freedom and the absolute will of God, trend  of thought religious leaders in North Bengkulu more directed to understanding of the authority and the absolute will of God, as to which are held by Asy’ariyah understand, because humans trying to be balanced with the absolute power  of God. Human  beings  are  not creation that  freely, but free man  limited  by God as a limited  human being with age. This indicates that humans are limited and everything has an end. Thought religious leaders in North Bengkulu  on qadha and qhadar which  are already  provisions  inviolability, humans could  only surrender and  resignation to God. Thus they tend  to be closer  to understanding Asy’ariyah. Thought  religious leaders on the  nature  of God, they adopts Asy’ariyah, they’ve studied the  attributes of God. By reading  and  realize  their self-interest as human beings  would  study the nature  of God, then  verily Allah can describe it is there.  Factors affecting patterns of thought  religious leaders of the Islamic theology in North Bengkulu,  namely  their learning that be a forum to understand the Islamic faith, boarding schools  in Bengkulu  Utara place  of formal education and non-formal and social situations such as differences in environmental conditions and impact of globalization very closely influence in shaping  the understanding of Islamic theology in North Bengkulu.